Characterization of Epithelial–Mesenchymal and Neuroendocrine Differentiation States in Pancreatic and Small Cell Ovarian Tumor Cells and Their Modulation by TGF-β1 and BMP-7 - Hendrik Ungefroren; Juliane von der Ohe; Rüdiger Braun; Yola Gätje; Olha Lapshyna; Jörg Schrader; Hendrik Lehnert; Jens-Uwe Marquardt; Björn Konukiewitz; Ralf Hass (Cells, 2024)
Pancreatic ductal adenocarcinoma (PDAC) has an extremely poor prognosis, due in part to early invasion and metastasis, which in turn involves epithelial–mesenchymal transition (EMT) of the cancer cells. Prompted by the discovery that two PDAC cell lines of the quasi-mesenchymal subtype (PANC-1, MIA PaCa-2) exhibit neuroendocrine differentiation (NED), we asked whether NED is associated with EMT. Using real-time PCR and immunoblotting, we initially verified endogenous expressions of various NED markers, i.e., chromogranin A (CHGA), synaptophysin (SYP), somatostatin receptor 2 (SSTR2), and SSTR5 in PANC-1 and MIA PaCa-2 cells. By means of immunohistochemistry, the expressions of CHGA, SYP, SSTR2, and the EMT markers cytokeratin 7 (CK7) and vimentin could be allocated to the neoplastic ductal epithelial cells of pancreatic ducts in surgically resected tissues from patients with PDAC. In HPDE6c7 normal pancreatic duct epithelial cells and in epithelial subtype BxPC-3 PDAC cells, the expression of CHGA, SYP, and neuron-specific enolase 2 (NSE) was either undetectable or much lower than in PANC-1 and MIA PaCa-2 cells. Parental cultures of PANC-1 cells exhibit EM plasticity (EMP) and harbor clonal subpopulations with both M- and E-phenotypes. Of note, M-type clones were found to display more pronounced NED than E-type clones. Inducing EMT in parental cultures of PANC-1 cells by treatment with transforming growth factor-β1 (TGF-β1) repressed epithelial genes and co-induced mesenchymal and NED genes, except for SSTR5. Surprisingly, treatment with bone morphogenetic protein (BMP)-7 differentially affected gene expressions in PANC-1, MIA PaCa-2, BxPC-3, and HPDE cells. It synergized with TGF-β1 in the induction of vimentin, SNAIL, SSTR2, and NSE but antagonized it in the regulation of CHGA and SSTR5. Phospho-immunoblotting in M- and E-type PANC-1 clones revealed that both TGF-β1 and, surprisingly, also BMP-7 activated SMAD2 and SMAD3 and that in M- but not E-type clones BMP-7 was able to dramatically enhance the activation of SMAD3. From these data, we conclude that in EMT of PDAC cells mesenchymal and NED markers are co-regulated, and that mesenchymal–epithelial transition (MET) is associated with a loss of both the mesenchymal and NED phenotypes. Analyzing NED in another tumor type, small cell carcinoma of the ovary hypercalcemic type (SCCOHT), revealed that two model cell lines of this disease (SCCOHT-1, BIN-67) do express CDH1, SNAI1, VIM, CHGA, SYP, ENO2, and SSTR2, but that in contrast to BMP-7, none of these genes was transcriptionally regulated by TGF-β1. Likewise, in BIN-67 cells, BMP-7 was able to reduce proliferation, while in SCCOHT-1 cells this occurred only upon combined treatment with TGF-β and BMP-7. We conclude that in PDAC-derived tumor cells, NED is closely linked to EMT and TGF-β signaling, which may have implications for the therapeutic use of TGF-β inhibitors in PDAC management.